Zooplankton vertical stratification in the East-pacific and Indian sectors of the Southern Ocean - Liu, Yunzhe; Wang, Yanqing; Sun, Yongming; Yang, Guang; Swadling, Kerrie M. (Frontiers in Marine Science, 2024)
The vertical structure, including abundance and composition, of zooplankton and associated environmental drivers in Antarctic waters is not well understood, particularly in the mesopelagic and upper bathypelagic layers. Depth-stratified zooplankton samples were collected from 0 to 1500 m during four summers in the East-Pacific and Indian sectors of the Southern Ocean. In addition, analysis of environmental drivers including temperature, salinity, dissolved oxygen, and chlorophyll a concentration, as well as water masses was conducted. Our study indicates that zooplankton diversity may be similar between the two sectors, while zooplankton abundance was higher in the East-Pacific sector during different sampling months and years. Moreover, zooplankton abundance decreased with depth in both sectors. Based on cluster analysis, zooplankton communities were generally divided by either the epipelagic or the deeper layers communities. In both sectors, the epipelagic layer was dominated by cyclopoid copepods, such as Oithona similis and Oncaea curvata, as well as calanoid copepods including Calanoides acutus, Rhincalanus gigas, and Ctenocalanus citer, while copepods and other taxa including Chaetognatha, Amphipoda, and Ostracoda, were important contributors to the deep layer communities. Our statistical analysis revealed that water masses, combined with their physical characteristics such as specific temperature, salinity ranges, and depth, along with biological factors such as chlorophyll a concentration, are important drivers for structuring zooplankton communities. Additionally, the vertical distribution patterns of zooplankton align with the biotic properties of different water masses or layers, such as food availability.